Penerapan Model Flipped Learning Berbantuan PPT Interaktif di Kelas 4 SDN Sungai Miai 5 - Fidya Aisyah Asyifa; Ifanda Rahmadani; Shofiatun Najiah; Aldy Ferdiyansyah; Asniwati Asniwati (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Students are individuals who are in the process of learning and developing themselves through formal and non-formal education. There are still teachers who do not pay attention to the initial conditions of students before learning begins, so that it has an impact on the learning outcomes obtained. This article aims to explain the application of flipped learning model assisted by interactive PowerPoint media in improving learning effectiveness in class IV SDN Sungai Miai 5. This research uses descriptive qualitative method with data collection techniques in the form of observation, interviews, and documentation. Interviews were conducted with four informants, namely homeroom teachers and three students. Observations were conducted in a participatory manner, while documentation included classroom learning activities and teacher teaching styles. The data obtained were analyzed in depth. The results showed that grade IV students expect fun, interesting, and active learning. The flipped learning model assisted by interactive PowerPoint is proven to help create a more effective learning atmosphere. Future research is suggested to examine the application of this model in other grade levels or subjects to broaden the understanding of its effectiveness in various learning contexts.